Role of DNA methylation in hybrid vigor in Arabidopsis thaliana - Kawanabe, Takahiro (Proc Natl Acad Sci U S A, 2016)
Hybrid vigor or heterosis refers to the superior performance of F(1) hybrid plants over their parents. Heterosis is particularly important in the production systems of major crops. Recent studies have suggested that epigenetic regulation such as DNA methylation is involved in heterosis, but the molecular mechanism of heterosis is still unclear. To address the epigenetic contribution to heterosis in Arabidopsis thaliana, we used mutant genes that have roles in DNA methylation. Hybrids between C24 and Columbia-0 (Col) without RNA polymerase IV (Pol IV) or methyltransferase I (MET1) function did not reduce the level of biomass heterosis (as evaluated by rosette diameter). Hybrids with a mutation in decrease in dna methylation 1 (ddm1) showed a decreased heterosis level. Vegetative heterosis in the ddm1 mutant hybrid was reduced but not eliminated; a complete reduction could result if there was a change in methylation at all loci critical for generating the level of heterosis, whereas if only a proportion of the loci have methylation changes there may only be a partial reduction in heterosis.